Saffron a Prototype Example for Evidence Based Herbal Medicine - R Hajiaghaee; M Heidari; S Akhondzadeh (Institue of Medicinal Plants, ACECR, 2013)
Evidence-based medicine is now generally perceived to be the dominant operating system in conventional medicine. Evidence-based medicine developed concurrently with the internet and the world wide web. This is no coincidence since evidence-based medicine suggests a personal responsibility for clinicians to keep abreast of research that would be difficult without the information access that the web provides. Over the last two decades, evidence based herbal medicine has been considered as interesting field. One of prototype example of evidence base medicine is saffron. In this paper, we review saffron from evidence point of view.